Facile synthesis of the SnTe/SnSe binary nanocomposite via a hydrothermal route for flexible solid-state supercapacitors. Issue 18 (17th April 2023) - Abdullah, Muhammad; John, Peter; Fawy, Khaled Fahmi; Manzoor, Sumaira; Butt, Kashif Younas; Abid, Abdul Ghafoor; Messali, Mouslim; Najam-Ul-Haq, Muhammad; Ashiq, Muhammad Naeem
Abstract : CV at various scan rates and charge/discharge profile of the fabricated composite. Abstract : Environmental degradation and energy shortage are the two biggest problems facing the world right now. Because of the limited supply of non-renewable sources, the production of environment-friendly energy and its storage has gained significant importance. Pseudocapacitors have lately caught the interest of energy specialists due to their greater energy/power density and prolonged cycle life. In this work, binding-free SnTe/SnSe (STSS) electrodes deposited onto Ni foam (NF) as the conductive substrate have been developed by a facile hydrothermal route for supercapacitor applications. Several analytical tools were utilized to study the morphological, structural and textural characteristics. The electrochemical results obtained from a three-electrode system suggest that the STSS electrode material exhibits great specific capacitance ( C s ) of 1276 F g −1, specific energy ( E d ) of 46.45 W h kg −1 and specific power ( P d ) of 256 W kg −1 @ 1 A g −1 . The results of C dl indicate that the STSS (31.28 mF) has a larger C dl value than those of SnTe (23.22 mF) and SnSe (26.35 mF). The analysis of electrochemical stability indicates that the STSS displays structural stability over 5000 cycles with a maximum capacitance retention of 96%. The Nyquist plot profile displayed a smaller R ct value for STSS (0.89 Ω) than SnSe (1.13 Ω) and SnTe (1.97 Ω). The symmetric behavior of STSS was determined in 2.0 M potassium hydroxide. The results reveal that this material has a specific capacitance of 537.72 F g −1 and specific energy of 78.32 W h kg −1 . These findings suggest that the STSS electrode might serve as a potential candidate for supercapacitors and other energy-saving equipment.